Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1977
DOI: 10.1002/ajh.2830020303
|View full text |Cite
|
Sign up to set email alerts
|

Successful transfusion of platelets “mismatched” for HLA antigens to alloimmunized thrombocytopenic patients

Abstract: A critical factor limiting the availability of histocompatible platelet transfusions for alloimmunized, thrombocytopenic patients is the large pool of HLA-typed donors needed to procure platelets perfectly matched for HLA antigens. We have, therefore, investigated the effectiveness of platelets obtained from donors having lesser degrees of histocompatibility. In 421 transfusions administered to 59 alloimmunized patients who were refractory to "random donor" platelets, it was found that platelets mismatched for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
83
0
1

Year Published

1980
1980
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(84 citation statements)
references
References 21 publications
0
83
0
1
Order By: Relevance
“…O objetivo desta terapêutica foi alcançar um melhor incremento plaquetário, baseado na compatibilidade HLA. 20 Os dados citados na literatura revelam que a manutenção ideal da hemoglobina dos pacientes seria níveis hematimétricos superiores a 9 g/dL 2 , muito embora, nos pacientes deste estudo tenhamos adotado como referência a transfusão de concentrados de hemácias durante o período de aplasia medular, o equivalente a 10 g/dL de hemoglobina, e a decisão para a transfusão de concentrados de plaquetas, baseada no seu uso terapêutico ou profilático. Vamos de encontro com os dados fornecidos pela literatura sobre controvér-sias que ainda persistem a respeito da melhor dose a ser utilizada e da apropriada contagem plaquetária para pacientes hemostaticamente controlados e sem evidências de…”
Section: Discussionunclassified
“…O objetivo desta terapêutica foi alcançar um melhor incremento plaquetário, baseado na compatibilidade HLA. 20 Os dados citados na literatura revelam que a manutenção ideal da hemoglobina dos pacientes seria níveis hematimétricos superiores a 9 g/dL 2 , muito embora, nos pacientes deste estudo tenhamos adotado como referência a transfusão de concentrados de hemácias durante o período de aplasia medular, o equivalente a 10 g/dL de hemoglobina, e a decisão para a transfusão de concentrados de plaquetas, baseada no seu uso terapêutico ou profilático. Vamos de encontro com os dados fornecidos pela literatura sobre controvér-sias que ainda persistem a respeito da melhor dose a ser utilizada e da apropriada contagem plaquetária para pacientes hemostaticamente controlados e sem evidências de…”
Section: Discussionunclassified
“…[3][4][5][6] When HLA-identical platelet donors are unavailable, the selection of HLA-matched or selectively mismatched platelet donors is based on the segregation of HLA antigens into serologically cross-reactive groups (CREGs). 7 Attention to linked HLA specificities (Bw4/Bw6) is beneficial in some patients unresponsive to cross-reactive platelets, while mismatching for poorly expressed HLA-B locus antigens (eg, HLA-B44, B45) may be acceptable for certain donor-recipient pairs. 8,9 These broad strategies have been implemented to decrease the size of the donor pool required to support all alloimmunized patients with matched products.…”
Section: Introductionmentioning
confidence: 99%
“…However, this strategy is not always successful; previous studies report unsatisfactory increments in up to 40% of CREG-matched transfusions. [7][8][9][10] The probability of finding 4 antigen-matched or CREG-matched products for patients with uncommon HLA phenotypes is low. Also, CREG matching gives more importance to public epitopes over private epitopes and is based on serologic data that has been largely supplanted by our current understanding of HLA polymorphisms at the structural level.…”
Section: Introductionmentioning
confidence: 99%
“…As one example, there is a high degree of serologic cross-reactivity amongst many of the HLA antigens and it was shown that one could mismatch for these similar antigens thereby increasing the number of donors available. 4 Other antigens, such as HLA B44 and 45, have weak expression on platelets such that platelets mismatched for these common antigens might not be cleared even if antibody against these antigens was present. 5 Indeed, these strategies proved to be of benefit in approximately 75% of alloimmunized recipients.…”
mentioning
confidence: 99%